2018
DOI: 10.1590/2317-6431-2016-1786
|View full text |Cite
|
Sign up to set email alerts
|

Treinamento auditivo computadorizado em idosos protetizados pelo Sistema Único de Saúde

Abstract: RESUMO Objetivo Verificar a efetividade de um programa de treinamento auditivo computadorizado em idosos protetizados. Métodos O estudo foi realizado com 72 idosos, entre 60 e 89 anos de idade, média de 74 anos (±7,8), protetizados em um centro de saúde. Os participantes foram divididos em grupo experimental, 48 (66,7%) e grupo controle, 24 (33,3%). Todos foram submetidos aos testes comportamentais (Fala no Ruído, Random Gap Detection Test e Dicótico de Dígitos) e ao questionário de restrição de participaç… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 20 publications
0
4
0
3
Order By: Relevance
“…Regarding the monotic test used in the study (Speech in Noise), it was possible to observe an improvement on the comparison of the percentages at the two distinct assessment moments, with significant difference bilaterally. Other studies 3,13,18,30 also demonstrated the effectiveness of the auditory rehabilitation on the results of the abilities of figure-ground and auditory closure for verbal sounds.…”
Section: Discussionmentioning
confidence: 80%
“…Regarding the monotic test used in the study (Speech in Noise), it was possible to observe an improvement on the comparison of the percentages at the two distinct assessment moments, with significant difference bilaterally. Other studies 3,13,18,30 also demonstrated the effectiveness of the auditory rehabilitation on the results of the abilities of figure-ground and auditory closure for verbal sounds.…”
Section: Discussionmentioning
confidence: 80%
“…Computer-based auditory training program was found to be effective and can improve the overall hearing abilities [25]. Gonzalez-Garrido et al [6] found that training increases P300 amplitudes in both normal and deaf patients.…”
Section: Discussionmentioning
confidence: 99%
“…According to the creators of the (11) method, rehabilitation by means of cognitive auditory training enables neuronal reorganization, by virtue of neuroplasticity, reducing in patients the complaints related to auditory and cognitive abilities. Studies show that the combination of auditory and cognitive tasks, when included in auditory training, provides a more efficient intervention (22,26) .…”
Section: Discussionmentioning
confidence: 99%
“…When observing the age range item, we observed an average of middle-aged adults; the subjects with higher age were the ones who presented the least differences in the pre-and post-auditory training (Figures 1 and 2). This can happen because of the gradual aging process, in which information processing slows down, that is, the brain of older adults is slower and needs a longer period of time for neuronal reorganization to occur in an efficient way (25,26) .…”
Section: Discussionmentioning
confidence: 99%